Instrumento para coleta de dados ao idoso institucionalizado com declínio cognitivo - Nascimento, Neyce de Matos (2019)
Introduction: Nursing care for institutionalized elderly people with cognitive decline must take place in order to meet all their needs, seeking to provide quality and individuality in care provision. Objective: To construct an instrument for data collection from the nursing consultation directed to the institutionalized elderly person with cognitive decline based on Wanda Horta’s Theory. Method: This was a methodological research carried out in two Long-Term Institutions for Elderly People Vila Vicentina Júlia Freire and Lar da Providência, in three stages: 1) Identification of the empirical indicators of basic human needs of the institutionalized elders with cognitive decline, through a research with mixed methods of the explanatory sequential type. Initially, a quantitative survey was conducted with 90 elderly people, which allowed screening 62 elderly people with cognitive decline, through the application of the Mini-Mental State Examination. The qualitative research was then carried out through three focus groups, consisting of one group of seven elderly people with cognitive decline, and the other two groups, with 11 caregivers of elderly people with cognitive decline, distributed as follows: a nurse; three nursing technicians and seven formal caregivers, to detect the indicators of basic human needs of the elders with cognitive decline. In step 2, the data collection instrument was elaborated and in step 3, the content and appearance of the data collection instrument were validated by eight nurses specialized in the postulated area. Results: 91 indicators of basic human needs were identified, of which 67 belong to psychobiological needs, 22 to psychosocial needs and two to psycho-spiritual needs. The specialist nurses carried out the validation of 85 indicators of basic human needs; 25 content validation items related to the sociodemographic aspect, service data and care provision and appearance validation. All validated items obtained agreement validity index above 0.80. Final Thoughts: The construction of the instrument of nursing consultation for the institutionalized elderly person with cognitive decline should allow advancements in the implementation of Nursing Care Systematization in long-term institutions, providing a higher quality of care.